Considering Blood Dilution improves the Precision of Continuous Whole Blood Glucose Measurements. (July 2019) - Benesch, Carsten; Kuhlenkötter, Mareike; Heise, Tim
Background: One major advantage of automated over manual clamps are continuous measurements of blood glucose concentrations (BG) allowing frequent adaptations in glucose infusion rates (GIR). However, BG measurements might be affected by changes in blood dilution. ClampArt®, a modern automated clamp device, corrects BG measurements for blood dilution, but the impact of this correction is unclear. Methods: The authors performed a retrospective analysis of BG during glucose clamps comparing values with a fixed dilution factor with those corrected for the actual blood dilution. Results: Clamp quality substantially improved with the consideration of blood dilution: Mean accuracy fell from 8.1% ± 2.9% to 4.1% ± 0.8%, precision improved from 9.6 ± 3.6 mg/dl to 3.7 ± 1.3 mg/dl and control deviation from −2.6 ± 4.2 mg/dl to 0.2 ± 0.2 mg/dl. Conclusions: Correcting continuous BG measurements for blood dilution significantly increases BG measurement and clamp quality.